Geochemistry Signature and K-Ar Age of the I-type Granite at East Coast of Bangka Island - Ronaldo Irzon; Muhammad Zulfikar; Udaya Kamiludin; Noor Cahyo Dwi Aryanto; Deny Setiadi; Yogi Noviadi; Undang Hernawan (Indonesian Journal on Geoscience, 2023)
This work presents microscopic-, whole-rock geochemical- , and K-Ar age data for Tanjung Berikat Granitoid at the easternmost part of Bangka Island. Some selected samples are in the range of monzogranite and granodiorite based on microscopic analysis. The rocks are characterized by a wide range in SiO2 (62.75 - 70.17 wt %), high-K calcalkaline to shoshonitic affinity, and ferroan signature. Very good correlation values of bivariate SiO2 plotted against other major oxides, similar spider diagrams normalized to the composition of the N-MORB and chondrite-normalized REE diagrams demonstrate the same origin and crystallization mechanism of the granitoid. The I-type nature of the studied granite is based on the hornblende existence, metaluminous character, negative SiO2 to P2O5 correlation, and volcanic arc characteristics of the rock. Tanjung Berikat Granitoid was crystallized in the mid ̶ late Early Cretaceous at 125.5 ± 2.8 Ma and 109.4 ± 2.5 Ma based on the K-Ar dating method. Keywords: granitoid, geochemistry, I-type, Bangka Island